Energy Drink Perception, Consumption, And Knowledge Level Among University Students (A Case At Agricultural Faculty, The University Of Brawijaya) - Lygi, Yasmin; Hartono, Rachman; Prasetyaningrum, Dian Islami (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2024)
Energy drinks containing caffeine, taurine, and other vitamins and minerals are popular among Indonesians, especially students, for their claimed benefits of increased energy, concentration, and alertness. The hype of assignments acquired by a student made them the habit of staying awake at night and boosting their energy during exams and assignments, which exacerbated that potential consumption. However, excessive and continuous consumption of these drinks can lead to harmful effects, such as kidney disorders. Descriptive quantitative methods were used to analyze data obtained by 140 agriculture students at Brawijaya University through an online questionnaire by G-Form. The relationship was tested using Chi-Square and SPSS software. The result shows that the level of energy drink consumption among students is relatively low, with a proportion of 22.14% from 140 respondents. A Chi-square test was performed to analyze the relationship between consumption level and gender with a p-value of 0.000, indicating a significant difference between consumption level and gender. Respondents' perceptions of energy drinks tend to be evenly distributed, as the proportions are almost equal. The majority of respondents have a low level of knowledge regarding energy drinks. This is evidenced by the proportion of respondents with a low level of expertise, which is 80%. The knowledge level analysis about consumption level yielded a p-value of 0.722, indicating no significant difference. When reclassified based on gender, it shows a p-value of 0.002 for low knowledge level and a p-value of 0.046 for high knowledge level, which means gender is not a moderate variable.